Fan Beam Tomography Technique for Scale Thickness Measurement in Geothermal Pipeline West Java Area - Wibisono Wibisono; Firliyani Rahmatia Ningsih; Paston Sidauruk; Sastra Wijaya Kusuma (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2020)
In the industrial field, tomography technique has been developed for inspection or maintenance by obtaining cross-sectional images of an object. Tomography application in geothermal power plant assist online inspection without interrupting operation process. Identification of scale materials in online condition is required to observe steam pipe productivity. A fan beam computed tomography system using gamma-ray transmission has been developed in laboratory experiment and field work. The aim of this study is to identify scale materials and its’ parameters, for instance geometry, density, and concentration of elements. The system feature is an arc up to 100°, vertex distance of 413.5 mm, fan rotation increment of 2.813°, and fan sensor spacing of 0.781°. This auto control system is used to scan geothermal pipe with outer diameter (OD) of 220 mm and thickness of 8.18 mm. Gamma radiation source which used is Scandium-46 (Sc-46) with activity 15 mCi. In this paper, experiment data are compared with Monte Carlo simulation method to strengthen interpretation. The results showed that image reconstruction successfully identify geometry and distribution scale materials inside the pipe which is the thickest located in d position 62 mm. Element analysis tested using neutron activation analysis (NAA) method contain some elements, with confidence level 95%.